Peran Pendidikan Kewarganegaraan dalam Menjaga Identitas Nasional - Naura Salsabila; Zahwatun Habibah; Sofia Ramadhani (Jurnal Pengetahuan Sosial dan Sejarah, 2025)
Civic education plays a crucial role in maintaining national identity. In the context of Indonesia, which is rich in cultural and ethnic diversity, civic education serves as a forum for instilling national values ​​and collective awareness. This study aims to identify how civic education can contribute to strengthening national identity. The methods used are literature studies and qualitative analysis of various relevant sources. The results of the study indicate that civic education can strengthen the sense of nationality and national unity, but also requires adjustments to deal with the ever-evolving social and cultural dynamics.